Organized waste disposal in the Pottery Neolithic: A bifacial workshop refuse pit at Ein Zippori, Israel. (1st November 2016) - Agam, Aviad; Walzer, Naama; Schechter, Heeli C.; Zutovski, Katia; Milevski, Ianir; Getzov, Nimrod; Gopher, Avi; Barkai, Ran
Abstract : A unique Pottery Neolithic context corresponding to the Wadi Rabah culture was found at the multi-layered site of Ein Zippori, Israel. Given the significant amount of flakes, cortical flakes, thinning flakes, and bifacial tool rejects, it was classified as a refuse pit in which bifacial knapping waste from a nearby workshop was disposed. In this paper we present the assemblage of Locus 8071, focusing on the by-products of bifacial tool manufacture and maintenance as well as bifacial tool rejects. We reconstruct the bifacial knapping and maintenance procedures and suggest that Locus 8071 was a disposal area for by-products from a knapping workshop of bifacial tools—an aspect of spatial organization related to possible specialized lithic production at Ein Zippori during the Neolithic period.